2019
DOI: 10.14260/jemds/2019/722
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Telenursing on Health Promoting Behaviours of Haemodialysis Patients in Education Hospitals in Zahedan in 2017-2018

Abstract: A B S T R A C T BACKGROUNDThe main goal of treatment and care of chronic patients including patients with chronic kidney failure undergoing haemodialysis is to promote their health. This study has been performed with the aim of examining the effect of tele-nursing on health promoting behaviours of haemodialysis patients in educational hospitals of Zahedan city in 2017-2018. METHODSThis quasi-experimental study was performed on patients undergoing haemodialysis who qualified the inclusion criteria. The number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 12 publications
0
11
0
2
Order By: Relevance
“…Evidence indicates that intervention programs have effectively improved HPBs in patients with different diseases ( Dashti et al, 2016 , Shahsavani and Kiani, 2019 ); however, such programs have less been implemented in patients with MS. Shahsavani et al (2018) reported that educational intervention about dialysis diet could improve health behaviors in patients under dialysis ( Shahsavani and Kiani, 2019 ). In a study on cancer patients, nursing interventions affected health promoting behaviors in cases that included health education and encouragement of change ( NMdSM et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence indicates that intervention programs have effectively improved HPBs in patients with different diseases ( Dashti et al, 2016 , Shahsavani and Kiani, 2019 ); however, such programs have less been implemented in patients with MS. Shahsavani et al (2018) reported that educational intervention about dialysis diet could improve health behaviors in patients under dialysis ( Shahsavani and Kiani, 2019 ). In a study on cancer patients, nursing interventions affected health promoting behaviors in cases that included health education and encouragement of change ( NMdSM et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dehdari et al (2014) presented evidence that an intervention based on Pender's model could improve Iranian students' consumption of nutrients ( Dehdari et al, 2014 ). Shahsavani et al’s study (2015) on hemodialysis patients showed an improvement in adherence to diet through patient education and telephone follow-up (telenursing) ( Shahsavani and Kiani, 2019 ). Zheng et al (2020) reported that a combination of face-to-face education and quarterly telephone follow-up could improve self-efficacy for nutrition, stress dimension, and the total score of HPBs ( Zheng et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polônia/Inglês VI Estudo exploratório com abordagem quantitativa A9 (22) Irã/Inglês III Quase experimental A10 (23) Irã/Inglês III Quase experimental A11 (24) Irã/Inglês III Quase experimental A12 (25) Estados Unidos/Inglês VI Revisão integrativa A13 (26) Brasil/Português VI Revisão integrativa A14 (27) Suécia/Inglês IV Estudo de coorte A15 (28) Brasil/Português VI Revisão integrativa A16 (29) Brasil/Português VI Descritivo, com abordagem qualitativa A17 (30) Holanda/Inglês III Quase-experimental A18 (31) Irã/Inglês II Ensaio clínico controlado randomizado A19 (32) Brasil/Português II Ensaio clínico randomizado A20 (33) China/Inglês II Ensaio clínico randomizado A21 (34) Chile/Inglês VI Revisão integrativa A22 (35) França/Inglês II Ensaio clínico randomizado A23 (36) Brasil/Português VI Artigo metodológico A24 (37) Alemanha/Inglês VI Estudo transversal com abordagem quantitativa A25 (38) Brasil/Português V Revisão sistemática A26 (39) Estados Unidos/Inglês III Quase-experimental A27 (40) Estados Unidos/Inglês II Ensaio clínico randomizado A28 (41) Inglaterra/Inglês IV Estudo prospectivo com abordagem quantitativa A29 (42) Irã/Inglês II Ensaio clínico controlado randomizado A30 (43) Brasil/Português VI Revisão integrativa A31 (44) Estados Unidos/Inglês VI Revisão integrativa A32 (45) Irã/Inglês VI Estudo exploratório com abordagem quantitativa A33 (46) Irã/Inglês III Quase-experimental A34 (47) Irã/Inglês VI Estudo qualitativo, descritivo A35 (48) Irã/Inglês II Ensaio clínico controlado randomizado A36 (49) Irã/Inglês II Ensaio clínico randomizado duplo cego A37 (50) Alemanha/Inglês II Ensaio clínico controlado randomizado Figura 2 -Síntese dos artigos identificados. Fortaleza, CE, Brasil, 2021…”
Section: N°país/idiomaunclassified
“…No segundo eixo, a telenfermagem é definida como um subconjunto da telessaúde que se concentra na prestação, gestão e coordenação de cuidados e serviços que usam tecnologia de telecomunicações no domínio da enfermagem (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)42,(44)(45)(46)(47)(48)(49)(50) . É uma estratégia que proporciona uma inovação na prática de enfermagem na medida em que ampliam o escopo do exercício profissional para além do alcance físico com base no desenvolvimento de habilidades e conhecimentos específicos para aplicação dessa forma de cuidado (28) .…”
Section: Antecedentesunclassified